Dorothy Hansine Andersen The Life and Times of the Pioneering Physician-Scientist Who Identified Cystic Fibrosis - Baird, John Scott; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book chronicles the life and accomplishments of Dorothy Hansine Andersen, a pioneering American pathologist and pediatrician who was the first person to define, diagnose, and treat cystic fibrosis. Divided into three parts, the book begins by detailing Anderson$1 (Bs early life, including being orphaned as an adolescent, her college career, and her laborious start in the medical field. Part II then examines Andersen$1 (Bs role in defining the new disease (3z(Bcystic fibrosis of the pancreas(3y (Band her career of active engagement in various clinical pursuits and research, both in pathology and pediatrics. Chapters in this section also discuss the numerous attempts made by others to minimize Andersen$1 (Bs work through gender bias and the Matilda Effect. The book concludes by reviewing the foundations laid for CF, Andersen$1 (Bs legacy, and her terminal illness. Featuring an engaging narrative style, Dorothy Hansine Andersen is a historically relevant, invaluable text for anyone interested in the life of Dorothy Anderson and the nascence of cystic fibrosis diagnoses.s
Part I: Life before Babies Hospital -- Chapter 1: A beginning -- Chapter 2: Orphaned -- Chapter 3: College and medical school -- Chapter 4: False start -- Chapter 5: A reboot -- Part II: Babies Hospital during the McIntosh Era -- Chapter 6: Historical perspectives -- Chapter 7: Synergy -- Chapter 8: Andy$1 (Bs abandoned farm -- Chapter 9: Scoring the first goal -- Chapter 10: CF firsts -- Chapter 11: (3z(BTo Dr. Andersen who has pulled me through many a tough year(3y (B-- Chapter 12: McIntosh, pediatric pathology, and Columbia University.-Chapter 13: CF sweat and the Matilda Effect -- Chapter 14: Glycogen storage diseases -- Chapter 15: Celiac disease -- Chapter 16: Randomized, controlled trials -- Chapter 17: Babies Hospital siblings -- Chapter 18: A last decade of CF research -- Chapter 19: Pediatric heart diseases -- Part III: Beyond Babies Hospital and the McIntosh Era -- Chapter 20: Time to enjoy the view -- Chapter 21: A foundation and a club for CF -- Chapter 22: The end of an era -- Chapter 23: Cancer.s
Keywords: Internal medicine; Pediatrics; Internal Medicine; Pediatrics; Andersen, Dorothy H (Dorothy Hansine), 1901-1963; Pediatricians; Biography; History